The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.bbrc.2007.07.105
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow supports human islet β cell survival and function over six months

Abstract: In this study, we have established a new strategy increasing human islet longevity utilizing allogeneic whole bone marrow (BM) co-cultured with human islets. The cultured islets' function and survival have been evaluated by analysis of insulin secretion in response to high-glucose-challenge, morphological evaluation of cell growth. Human islet only culture failed to reveal evidence of long term survival, growth or function in terms of insulin release or insulin response to glucose challenge. These results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
(14 reference statements)
0
46
1
Order By: Relevance
“…Human islet tissue from normal donors was obtained through the Islet Resource Centers (ICRs) Basic Science Islet Distribution Program from the Human Islet Laboratories at the University of Pennsylvania (Philadelphia, PA, USA), Massachusetts General Hospital (Boston, MA, USA), City of Hope National Medical Center (Duarte, CA, USA), University of Miami, School of Medicine, Diabetes Research Institute (Miami, FL, USA). The use of these cells is approved by the Institutional Review Board (IRB) at Roger Williams Hospital and the ICR Committee [9].…”
Section: Tissue and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Human islet tissue from normal donors was obtained through the Islet Resource Centers (ICRs) Basic Science Islet Distribution Program from the Human Islet Laboratories at the University of Pennsylvania (Philadelphia, PA, USA), Massachusetts General Hospital (Boston, MA, USA), City of Hope National Medical Center (Duarte, CA, USA), University of Miami, School of Medicine, Diabetes Research Institute (Miami, FL, USA). The use of these cells is approved by the Institutional Review Board (IRB) at Roger Williams Hospital and the ICR Committee [9].…”
Section: Tissue and Cell Culturementioning
confidence: 99%
“…Trypan blue (Gibco, 15250-061) staining was used to assess cell viability. The use of these cells is approved by the Institutional Review Board (IRB) at Roger Williams Hospital and the ICR Committee [9].…”
Section: Tissue and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant transplantation of islets with BM stem cells, vascular endothelial cells, endothelial progenitor cells (EPCs) and MSCs creates a suitable niche for promotion of revascularization and enhancement of grafted islet survival and function (123,124,125,126).…”
Section: Enhancement Of Islet Vasculaturementioning
confidence: 99%
“…On the other hand, most studies have shown beneficial effects of cellular and cytokine interventions on islet remodeling and recovery from injury without significant conversion to produce insulin (8,12,19,33,39,40,42,45,66,68).…”
Section: Introductionmentioning
confidence: 99%